2016
DOI: 10.5603/ait.a2016.0035
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of non-endoscopic and endoscopic adhesiolysis of epidural fibrosis

Abstract: Low back and leg pain may be due to many causes, one of which is scarring in the epidural space. Epidural scarring may provoke this pain for many reasons: nerves may be trapped by scars, while veins in the epidural space press down upon the nerves and become enlarged, putting pressure on the nerves. Endoscopic and percutaneous epidural adhesiolysis allows one to eliminate the deleterious effects of scar formation, which can both physically prevent the direct application of drugs to nerve and provide relief in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Another study demonstrated the effectiveness of epidural nerve adhesiolysis for low back and leg pain regardless of type of lumbar disc herniation ( 25 ). Other studies ( 26 , 27 ) have focused on comparing physical therapy and epidural anaesthesia based on the assumption that epidural adhesiolysis has only an interventional role, but the data support the definite presence of adhesions even in preoperative patients with lumbar spinal stenosis or lumbar disc herniation. In addition, Yokosuka et al performed epidural contrast imaging and evaluated CT in patients who had undergone adhesion release for severe lower back pain ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated the effectiveness of epidural nerve adhesiolysis for low back and leg pain regardless of type of lumbar disc herniation ( 25 ). Other studies ( 26 , 27 ) have focused on comparing physical therapy and epidural anaesthesia based on the assumption that epidural adhesiolysis has only an interventional role, but the data support the definite presence of adhesions even in preoperative patients with lumbar spinal stenosis or lumbar disc herniation. In addition, Yokosuka et al performed epidural contrast imaging and evaluated CT in patients who had undergone adhesion release for severe lower back pain ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is concordant with our finding that RF addes a benefit to the management of FBSS. Bellini and Barbieri [14] treated the cases of low back pain due to many causes; one of them is scarring in the epidural space. The success rate of epidural steroid injections in dealing with epidural fibrosis has been reported to be 59% and 58% at one and two years, considering 4 and 5 procedures during this period.…”
Section: Group IImentioning
confidence: 99%